Being With Technology – Truth, History, Disclosure (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
The aim of this paper is to illuminate a phenomenon that is constitutive of being human, and that is in danger of being lost or forgotten in our current technological age: the phenomenon of being receptive to the world. Some problems and possible solutions to this are highlighted, along with a proposed answer.
Keywords: Technology; ordering; controlling; optimising; receptivity; understanding; being; nihilism; truth; history; disclosure